2021
DOI: 10.1021/acssensors.1c01470
|View full text |Cite
|
Sign up to set email alerts
|

Glycan-Based Flow-Through Device for the Detection of SARS-COV-2

Abstract: The COVID-19 pandemic, and future pandemics, require diagnostic tools to track disease spread and guide the isolation of (a)symptomatic individuals. Lateral-flow diagnostics (LFDs) are rapid and of lower cost than molecular (genetic) tests, with current LFDs using antibodies as their recognition units. Herein, we develop a prototype flow-through device (related, but distinct to LFDs), utilizing N- acetyl neuraminic acid-functionalized, polymer-coated, gold nanoparticles as the detection/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 69 publications
(107 reference statements)
0
28
0
Order By: Relevance
“…It was not possible to find a commercially available BSA-glycoconjugate with sufficient affinity for RCA 120 to generate a test line. Therefore, an alternative approach, a “flow-through assay,” [ 40 , 52 , 53 ] was used based on direct deposition of the target (RCA 120 at 5 mg mL −1 ) onto the test line, followed by running the dipstick. Whilst unconventional, we have previously used this methodology in S1 spike protein detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not possible to find a commercially available BSA-glycoconjugate with sufficient affinity for RCA 120 to generate a test line. Therefore, an alternative approach, a “flow-through assay,” [ 40 , 52 , 53 ] was used based on direct deposition of the target (RCA 120 at 5 mg mL −1 ) onto the test line, followed by running the dipstick. Whilst unconventional, we have previously used this methodology in S1 spike protein detection.…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 ] This clearly demonstrated that lateral flow glyco-assays, LFDs that use glycans as capture agents (on the test line and particle) for an analyte, have potential applications in rapid diagnostics, surveillance, and as accessible research tools for evaluating glycan-binding protein function. Further work utilizing a flow-through glyco-assay demonstrated that glycans could be used as capture agents to sense for the SARS-COV-2 virus in patient samples and that these tests were thermally robust, [ 40 ] which could be an advantage of glycan-based devices versus antibody-based devices. [ 41 ] To advance the study of glyco-LFD technology, LFDs that use glycans as capture agents on test lines and/or particles, it is crucial to understand how each component (particle, surface) impacts performance.…”
Section: Introductionmentioning
confidence: 99%
“…13A). 242 Controlled radical polymerisation (RAFT) was employed to undertake a detailed structure-function study exploring how the polymeric glyco tether impacted the performance of a lectin-detecting lateral flow system. 243 Using galactose as the glyco-ligand, the delicate balance between polymer chain length to give specificity, but avoid non-specific binding was revealed, demonstrated by differential binding profiles to SBA and RCA120 using the same glycan on different polymers (Fig.…”
Section: Lateral Flowmentioning
confidence: 99%
“…Fig.13Representative lateral flow glyco-assay and flow through glycoassay for sensing for SBA243 (A) and SARS-COV-2242 (B) respectively.…”
mentioning
confidence: 99%
“…20,21 Polymer-tethered sialic acidfunctionalised gold nanoparticles have been designed to bind the N-terminal domain of the SARS-CoV-2 spike protein, allowing for detection in lateral flow or liquid phase assays. [22][23][24] Similarly, lateral flow devices using heparin (which targets a different domain of the spike protein) have been demonstrated. 25 In these specific examples the glycosylated nanomaterials are exposed to nasal swab elutions, which have been diluted and hence components of the biological matrix (mucins etc.)…”
Section: Introductionmentioning
confidence: 99%